1999
DOI: 10.1002/(sici)1521-4168(19990301)22:3<144::aid-jhrc144>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Resolution of Conjugated Linoleic Acid Isomers by Tandem-Column Silver-Ion High Performance Liquid Chromatography

Abstract: A commercial mixture of conjugated linoleic acid (CLA) isomers, reportedly consisting of six components, was recently resolved into 12 peaks attributed to CLA isomers using silver‐ion high performance liquid chromatography (Ag+‐HPLC). In this study, the coupling of two analytical silver‐ion high performance liquid chromatography columns (tandem‐column Ag+‐HPLC) in series led to the enhanced resolution of CLA isomers. Many CLA isomers were baseline resolved and the pair 18 : 2 8,10 c/t and 18 : 2 7,9 c/t found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 22 publications
2
34
1
Order By: Relevance
“…The values given in this work for these grass-sensitive CLA isomers are higher than those reported for the mainland Portugal, which may reflect better quality of Azorean pastures in relation to the mainland Portugal [15]. Rickert et al [22] reported lower total trans/trans CLA isomers in cheese compared with the values described in this study. In addition, total trans/trans and cis/trans (cis/trans and trans/cis) CLA isomers in cheese were similar to those reported by Luna et al [16].…”
Section: Cla Isomeric Distributioncontrasting
confidence: 66%
“…The values given in this work for these grass-sensitive CLA isomers are higher than those reported for the mainland Portugal, which may reflect better quality of Azorean pastures in relation to the mainland Portugal [15]. Rickert et al [22] reported lower total trans/trans CLA isomers in cheese compared with the values described in this study. In addition, total trans/trans and cis/trans (cis/trans and trans/cis) CLA isomers in cheese were similar to those reported by Luna et al [16].…”
Section: Cla Isomeric Distributioncontrasting
confidence: 66%
“…Step Description of method References Analysis of FAME by GC (gas chromatography); results as g fatty acids per 100 g fat (not as esters) [10] 3b Analysis of CLA by Ag + -HPLC (high-performance liquid chromatography); results in g per 100 g fat [37,68] i: Integrated farming. a, b and c, d: Different letters within columns mean significant differences (P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…The isocratic mobile phase was 0.1% acetonitrile in n-hexane with a flow-rate of 1 ml/min. The injection volume was 20 µl as described by Rickert et al [22]. All conjugated compounds were detected at 234 nm with a photo diode array detector (200 to 400 nm, Waters PDA 996, Waters, Eschborn, Germany).…”
Section: Silver Ion High-performance Liquid Chromatography (Ag + -Hplc)mentioning
confidence: 99%